Identification of a Synthetic Polyhydroxyphenolic Resveratrol Analogue, 3,3′,4,4′,5,5′-Hexahydroxy-trans-Stilbene with Anti-SARS-CoV-2 Activity - Walter Jäger; Eva Kicker; Melina Hardt; Riem Gawish; Pia Gattinger; Michaela Böhmdorfer; Sylvia Knapp; Rudolf Valenta; Kurt Zatloukal; Thomas Szekeres (Molecules, 2023)
The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus has been causing the COVID-19 pandemic since December 2019, with over 600 million infected persons worldwide and over six million deaths. We investigated the anti-viral effects of polyphenolic green tea ingredients and the synthetic resveratrol analogue 3,3′,4,4′,5,5′-hexahydroxy-trans-stilbene (HHS), a compound with antioxidant, antitumor and anti-HIV properties. In the TCID50 assay, four out of nine green tea constituents showed minor to modest cell protective effects, whereas HHS demonstrated the highest reduction (1103-fold) of the TCID50, indicating pronounced inhibition of virus replication. HHS was also a highly effective inhibitor of SARS-CoV-2 proliferation in VeroE6 cells with an IC50 value of 31.1 µM. HSS also inhibited the binding of the receptor-binding domain (RBD) of the spike protein to the human angiotensin-converting enzyme 2 (ACE2) receptor (RBD-ACE2) binding with 29% at 100 µM and with 9.2% at 50 µM indicating that the SARS-CoV-2 inhibitory effect might at least in part be attributed to the inhibition of virus binding to ACE2. Based on the chemical similarity to other polyphenols, the oral bioavailability of HHS is likely also very low, resulting in blood levels far below the inhibitory concentration of EGCG against SARS-CoV-2 observed in vitro. However, administration of HHS topically as a nose or throat spray would increase concentrations several-fold above the minimal inhibitory concentration (MIC) in the mucosa and might reduce virus load when administered soon after infection. Due to these promising tissue culture results, further preclinical and clinical studies are warranted to develop HHS as an additional treatment option for SARS-CoV-2 infection to complement vaccines, which is and will be the main pillar to combat the COVID-19 pandemic.